Say goodbye - Gardner, Lisa. (Great Britain : Orion Paperback, 2008)
For Kimberly Quincy, FBI Special Agent, it all starts with a pregnant hooker. The story Delilah Rose tells Kimberly about her johns is too horrifying to be true--but prostitutes are disappearing, one by one, with no explanation, and no one but Kimberly seems to care
Keywords: United States. -- Officials and employees -- Fiction; Missing persons -- Fiction; Georgia -- Fiction; Mystery fiction